Notes on taxonomy and nomenclature of juno irises (Juno, Iridaceae) - Crespo, Manuel B.; Martínez-Azorín, Mario; Mavrodiev, Evgeny V. (Phytotaxa, 2018)
Juno (Iris subg. Scorpiris) is a distinct group of bulbous irises, widely diversified in central and southwestern Asia and the Caucasus with some representatives in the Mediterranean basin. It is a monophyletic group with remarkable morphological, biogeographical and molecular peculiarities, which is accepted here as an independent genus. In the present contribution, some taxonomic and nomenclatural issues are discussed, concerning several names of juno irises. As a result, ten new combinations are established (nine at specific rank and one at varietal rank), and the taxonomic relationships of some taxa are revisited. Types are indicated for all discussed names, of which one lectotype and two neotypes are designated here.